PENERAPAN ELECTRONIC GOVERNMENT (E-Gov) DALAM PENILAIAN KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH PROVINSI RIAU TAHUN 2018-2019 - Dela Meitika; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
E-Government is an information technology system developed by the Government to improve public services by providing options for the public to gain access to public information. The Riau Provincial Government has innovated to assess civil servants online through the legal basis of the Riau Governor Regulation Number 8 of 2018 concerning the Electronic Apparatus Performance Assessment System (E-SIKAP) in the Riau Province Government Environment. Electronic Performance Appraisal System, hereinafter referred to as e-SIKAP, is a bold-based system (in network) that can record and store data on targets and achievements of SKP PNS or CPNS connected to the PNS database. The assessment is used as the basis for payment of the salary system or it can be known as Additional Employee Income (TPP). The application of e-SIKAP helps to facilitate inputting and documenting elements of work performance. However, in reality many employees complained about the lack of socialization resulting in a lack of understanding of the employees of the new employee appraisal system. This study seeks to answer the following research questions, namely: what is the form of e-government application in the employee performance appraisal carried out by the Riau Province Regional Personnel Agency in 2018-2019, what factors affect the application of e-government in employee performance in the year 2018-2019. This study also aims to describe the application of e-government in employee performance appraisals in 2018-2019, then also to describe the factors that affect the application of e-government in employee performance appraisals in 2018-2019.This type of research used by the author in this study is descriptive. Data techniques are interviews, literature study and documentation. The data analysis technique in this study was conducted qualitatively. The results of this study explain that the application of E-Government in employee performance reports conducted by the Regional Personnel Agency of Riau Province is not optimal, because there are still complaints such as lack of socialization delivered by employees.Keywords: E-govt, E-govt to Employees, E-sikap.